2018
DOI: 10.1186/s41927-018-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of serum-derived exosomes in rheumatoid arthritis

Abstract: Background To understand the roles of serum exosomes in rheumatoid arthritis (RA), we comprehensively investigated the protein profiles of serum exosomes in patients with RA. Methods Exosomes were isolated from serum samples obtained from 33 patients (12 with active RA [aRA], 11 with inactive RA [iRA], 10 with osteoarthritis [OA]) and 10 healthy donors (HLs). Proteins extracted from the exosomes were separated by two-dimensional differential gel electrophoresis (2D-DIGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 40 publications
(52 reference statements)
1
24
0
1
Order By: Relevance
“…97 Tsuno et al extracted serum exosomal proteins from the healthy group, OA group and RA group and identified the exosomal proteins via 2D-DIGE and mass spectrometry methods. 247 They found that the exosomal protein profiles from the serum of the three groups were significantly different. There were 21 spots in the exosomal protein profiles with different intensities between the OA group and the healthy group, such as cathepsin F and Igalpha-2 chain C region, indicating the potential roles of these proteins in OA.…”
Section: Ultrafiltrationmentioning
confidence: 98%
See 1 more Smart Citation
“…97 Tsuno et al extracted serum exosomal proteins from the healthy group, OA group and RA group and identified the exosomal proteins via 2D-DIGE and mass spectrometry methods. 247 They found that the exosomal protein profiles from the serum of the three groups were significantly different. There were 21 spots in the exosomal protein profiles with different intensities between the OA group and the healthy group, such as cathepsin F and Igalpha-2 chain C region, indicating the potential roles of these proteins in OA.…”
Section: Ultrafiltrationmentioning
confidence: 98%
“…There were 21 spots in the exosomal protein profiles with different intensities between the OA group and the healthy group, such as cathepsin F and Igalpha-2 chain C region, indicating the potential roles of these proteins in OA. 247 Moreover, exosomal proteins have been revealed to participate in the exosome-mediated regulation of the biological response in chondrocytes. CD73/ecto-5′-nucleotidase was expressed in MSC-Exos.…”
Section: Ultrafiltrationmentioning
confidence: 99%
“…In another study [ 23 ], exosomes were isolated from serum samples obtained from 43 subjects: 12 with active RA, 11 with inactive RA, 10 with OA, and 10 healthy donors. Two hundred and four (204) protein spots were detected by 2D-DIGE; among them, the protein spot identified as Toll-like receptor 3 (TLR3) showed approximately 6-fold higher intensity in the active RA group than in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer precipitation-based isolation has the benefits of commercial availability and easy processing and is now widely applied to isolate EVs from the biofluids under many disease statuses, such as colorectal cancer, epithelial ovarian cancer, and rheumatoid arthritis [67,68,69]. This type of isolation method is initially used in viral studies by forming a polymer network to decrease the solubility of all components present in the sample [70].…”
Section: Isolation Strategies For Extracellular Vesicles In Ms-basmentioning
confidence: 99%